The Ontology of Montage and Beyond It - Milerius, Nerijus (Religija ir kultūra, 2012)
The article deals with the so-called pan-aesthetical ambition of montage (editing) according to which montage is not a merely technical element of a film, but the way to edit cinematic images, thinking, worldview, history, etc. It is argued that the origins of such pan-aesthetics of montage could be found primarily not in cinema itself. As an example of such pre-cinematographic notion of montage pan-aesthetics, a fragment of Gustave Flaubert’s Madame Bovary could be analyzed. It’s already in this fragment where the ambition of the literary montage to disclose much more than a simple literary description could manage is evident. Cinematic montage borrows this strategy and always declares the ambition to reach the limits of the visible and the presentable. Something that could not be depicted, the interval, becomes the means to go beyond the technical understanding of montage and to transform it into a peculiar form of thinking or exposition. It is argued in the article that such pan-aesthetic strategy is the very element of modernity. Referring to the excerpts from the films of Griffith and Eisenstein, it is demonstrated how the invisible (the interval) is used in the construction of the visible. The invisible (the interval) becomes the most essential criterion to classify the schools or types of montage.It is concluded that cinema abandons its ambition to transform the montage into the universal principle of constructing the whole. Nevertheless, also in the contemporary cinema, one could find the interpretations of montage according to which the montage is something more, something that surpasses the technical procedure of a mere editing.